Chilean National Sports Talent Detection System: Influence of Biological Age, Sex, and Geographic Area - Ariel Guevara-Araya; Samuel Curripan-Henríquez; Juan Aguilera-Julio; Ana Antinao-Soto; Oscar F. Araneda (Journal of Functional Morphology and Kinesiology)
The purpose of this study was to assess the methodology for selecting sports talent in the Chilean Promising Athletes Program (CPAP). Methods: The standing broad jump (SBJ), medicine ball chest throw (MBCT), thirty-meter running sprint (RS-30), Agility-T (T-test), and height were analyzed in 3060 schoolchildren from Chile, grouped by sex, age, geographical area (north, central and south) and maturity status at peak height velocity (PHV) in pre-, circa- and post-PHV. Results: Superior differences were found in boys for all age ranges in SBJ, RS-30, T-test, and MBCT (p < 0.05). Girls were taller than boys until the age of 12 years (p < 0.01) with a reversal of this trend after 13 years old (p < 0.001). In geographical grouping, higher scores in SBJ, RS-30, and T-test were found in the central zone for boys and girls (p < 0.05). In both sexes, higher scores for the northern zone in MBCT (p < 0.01) and height (p < 0.05) are observed. Among selected talents, when comparing post-PHV vs. pre-PHV the differences are superior in all tests for post-PHV in girls and for MBCT and height (p < 0.05) in boys. In circa-PHV vs. post-PHV in MBCT, T-test, and RS-30 only girls (p < 0.05) were superior in post-PHV. For pre-PHV vs. circa-PHV, RS-30, and height (p < 0.05), both sexes were superior in circa-PHV. There are differences between talents selected by physical tests and technical aspects (p < 0.05). Conclusions: The results show variations in physical and anthropometric tests in schoolchildren by age, sex, geography, and maturity status that should be considered for talent selection.